How user-friendly are user interfaces of open access digital repositories? - Vrana, Radovan (Array, 2010)
Digital information resources available on the Internet have become conditio sine qua non of modern research and teaching. In the last decade and a half the Internet and especially the Web had introduced many types of online information resources that emerged and vanished. Only those that were closely associated with important institutions in society (such as libraries and universities) and proved usable survived. Until recently, libraries have been places where university staff have sought quality information for research and teaching, and students for learning. With the proliferation of the Web, students have replaced libraries with search engines and they are now using them as primary tools for discovery of information necessary for completion of their written exams, term papers, presentations etc. In their effort to provide researchers, teachers and students with quality content, universities and libraries started development of digital repositories, digital archives of the intellectual product created by the faculty, research staff, and students of an institution. Digital repositories contain research data, journal articles, preprints, technical reports, books, theses and dissertations and other material used in research and educational process. The diverse content of digital repositories represents rich resources for research and teaching, In addition to the diversity and quality of the content, another issue – user interfaces – attracted attention of computer specialists because user interfaces are means of successful use of digital repositories. The research of top 20 open access digital repositories showed that the biggest repositories share common characteristics which help their users in their daily access to the content of repositories. Despite helpful similarities, some of these digital repositories should improve their design to become more attractive and attract younger generations of users seeking knowledge elsewhere on the Internet.